204k views
3 votes
5x-2y=14, 2x-y=5 substitution

User MiGo
by
5.8k points

1 Answer

5 votes

Answer:

The solution set is (4, 3)

Explanation:

To solve by substitution, start by solving the second equation for y.

2x - y = 5

-y = -2x + 5

y = 2x - 5

Now that we have this, put that expression in for y in the first equation and solve for x.

5x - 2(2x - 5) = 14

5x - 4x + 10 = 14

x + 10 = 14

x = 4

Now that we have the value of x, input it into either equation and solve for y.

2x - y = 5

2(4) - y = 5

8 - y = 5

-y = -3

y = 3

User Beeef
by
4.9k points